A Message Completion Quality in Subtitle Translation of Indonesia Foreign Affair Minister’s Speech - Tatu Siti Rohbiah; Ilzamudin; Suaidi, Afif; Teuku Adamsyah (Kirana Publisher (KNPub), 2022)
This research is to describe the message completion quality of the English – Bahasa Indonesia subtitle translation videos from six different channels and to describe the factors which motivate the message completion quality of the subtitle translation. The type of this research is included as qualitative research type adapted from linguistic research method, here is translational (identity) method (Sudaryanto, 2001). The content analysis method is employed specifically the semantic content analysis method and grammatical content analysis method. The research results show that there are four different channel videos that reach Very Excellent Quality i.e., CNN, KOMPAS, MoFA, and Tribun. Orderly, Tribun achieves the highest quality in both translation and completeness followed by MoFA, CNN, and then KOMPAS. In terms of completeness quality, Tribun is scored as the most complete both in technical limitation and in undelivered messages followed by MoFA, KOMPAS, and CNN, and their scores are very excellent. Although there is no mistake in the meaning accuracy, meaning clarity, and expression naturalness in terms of translation quality, both iNews RCTI, and TvOne, are good enough in terms of completeness. They both have no technical limitation problems but they have many undelivered messages.